Copy Number Signatures and Clinical Outcomes in Upper Tract Urothelial Carcinoma - Guan, Bao; Liang, Yuan; Lu, Huan; Xu, Zhengzheng; Shi, Yue; Li, Juan; Kong, Wenwen; Tian, Chuanyu; Tan, Yezhen; Gong, Yanqing; Liu, Jin; Fang, Dong; et al. (Frontiers in Cell and Developmental Biology, 2021)
Tumor staging of upper tract urothelial carcinomas (UTUC) is relatively difficult to assert accurately before surgery. Here, we used copy number (CN) signatures as a tool to explore their clinical significance of molecular stratification in UTUC. CN signatures were extracted by non-negative matrix factorization from the whole-genome sequencing (WGS) data of 90 Chinese UTUC primary tumor samples. A validation UTUC cohort (n=56) and a cohort from urinary cell-free DNA (cfDNA) of urothelial cancer patients (n=94) and matched primary tumors were also examined. Survival analyses were measured using Kaplan-Meier, and Cox regression was used for multivariate analysis. Here, we identified six CN signatures (Sig1-6). Patients with a high contribution of Sig6 (Sig6high), were associated with higher microsatellite instability level and papillary architecture, and had a favorable outcome. Patients with a low weighted genome integrity index, were associated with positive lymph node and showed the worst outcome. Sig6high was identified to be an independently prognostic factor. The predictive significance of CN signature was identified by a validation UTUC cohort. CN signatures retained great concordance between primary tumor and urinary cfDNA. In conclusion, our results reveal that CN signature assessment for risk stratification is feasible and provides a basis for clinical studies that evaluate therapeutic interventions and prognosis.